(untitled) (Proceedings of International Educators Conference, 2024)
This article is based on the fact that play is the type of activity that children take as an example of the social life of adults. The variety of subjects and content of creative games, which creates the need to describe them, the main component in the system of the plot game activity, including the character, life situation, action and the relationship of the characters, is analyzed.